Appearance and Reality in King Lear - Mariwan Hwayyiz Rustum (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
With fictional characters, every situation in life has its appearance and reality. The looks of things are sometimes what we would like to work out. The fact, what actually happens, isn't always clear to the observer. Folks that cannot break through the superficial appearance of things will only see what they require to believe. The fact during this situation is usually unattractive to the perceiver. These are the circumstances surrounding the conflict that transpire in William Shakespeare's fictional character. As an audience, you discover there's an enormous character flaw within the characters of King Lear and Earl of Gloucester. Within the story, neither of those two men manages to create the difference, in their minds, between what the people say and do, and what are the important motives of those two people behind their actions. This permits Lear and Gloucester to betray their own blood, becoming isolated from people who have their best interests inside. It's the lack to differentiate between appearance and reality that causes Lear and Gloucester to fall. In fictitious character, appearance or reputation determines the character. Edgar says lots in his soliloquy, when he disguises himself as poor Tom. There's a transparent contradiction between reality versus appearance. Reality is that the world or state of things as they really exist, Appearance could be a fantasy, and reality may be a gospel. In fiction, there are many characters that appear like they're not really. Since one cannot see the personality of the opposite, you'll be able to never identify someone for who they really are.